Evaluation of Mechanical Properties of Warm-Mix Asphalt Mixtures Prepared with Sasobit and Zeolite Additives - Wshyar M. Hasan; Rana A. Yousif; Saeid Hesami; Sady A. Tayh; Abbas F. Jasim; Hawkar H. Ibrahim (Directorate for Research and Community Services, Institut Teknologi Bandung, 2024)
This study aimed to evaluate the impact of different additive percentages on the mechanical properties and durability of warm-mix asphalt. Two types of additives, Sasobit as an organic additive and Zeolite as a water-based additive, along with bituminous foam, were used at 2%, 4%, and 6% levels in modified asphalt mixes. Rutting resistance, moisture susceptibility, and cracking resistance were assessed using semi-circular bending tests, dynamic creep tests, and indirect tensile strength tests, respectively. Additionally, a two-dimensional performance interaction diagram was developed. The results indicated that incorporating different percentages of Sasobit and Zeolite additives improved rutting and cracking resistance, respectively. Zeolite showed a positive impact on enhancing the resistance of the asphalt mixture against moisture susceptibility, while Sasobit had a negative effect. Moreover, the influence of these additives on mechanical performance intensified with increasing percentages. Notably, the mixture containing 6% Zeolite demonstrated the highest resistance to moisture susceptibility, while the mixture with 6% Sasobit showed the lowest. Furthermore, the performance interaction diagram results suggested that using 4% and 6% Zeolite along with 4% Sasobit is optimal for rutting and cracking resistance. Considering the degradation mechanisms of moisture susceptibility, rutting, and cracking, mixtures with 6% Zeolite and 4% Zeolite exhibited satisfactory performance against these factors.